NK‐cell receptors NKp46 and NCR1 control human metapneumovirus infection. Issue 4 (6th March 2017) - Diab, Mohammad; Glasner, Ariella; Isaacson, Batya; Bar‐On, Yotam; Drori, Yaron; Yamin, Rachel; Duev‐Cohen, Alexandra; Danziger, Oded; Zamostiano, Rachel; Mandelboim, Michal; Jonjic, Stipan; Bacharach, Eran; et al.
Abstract : HMPV infection induces changes in expression of ligands for NK cells. We show reduced MICA expression and an increase in expression of MHC‐I and an unknown ligand for NKp46/NCR1 following HMPV infection. Abstract : Natural killer (NK) cells are capable of killing various pathogens upon stimulation of activating receptors. Human metapneumovirus (HMPV) is a respiratory virus, which was discovered in 2001 and is responsible for acute respiratory tract infection in infants and children worldwide. HMPV infection is very common, infecting around 70% of all children under the age of five. Under immune suppressive conditions, HMPV infection can be fatal. Not much is known on how NK cells respond to HMPV. In this study, using reporter assays and NK‐cell cytotoxicity assays performed with human and mouse NK cells, we demonstrated that the NKp46‐activating receptor and its mouse orthologue Ncr1, both members of the natural cytotoxicity receptor (NCR) family, recognized an unknown ligand expressed by HMPV‐infected human cells. We demonstrated that MHC class I is upregulated and MICA is downregulated upon HMPV infection. We also characterized mouse NK‐cell phenotype in the blood and the lungs of HMPV‐infected mice and found that lung NK cells are more activated and expressing NKG2D, CD43, CD27, KLRG1, and CD69 compared to blood NK cells regardless of HMPV infection. Finally, we demonstrated, using Ncr1‐deficient mice, that NCR1 plays a critical role in controlling HMPV infection.